Role of Resistance to Innovation, Lack of Intercultural Communication, and Student Interest on the Student Demotivation Results Towards the English Education System - Wang, Jin; Pan, Lei (Frontiers in Psychology, 2022)
Recently, second language learning success depends upon the students' interest and motivation by adopting innovations that require regulators’ and new researchers’ emphasis. Hence, the present article explores the role of resistance to innovation, lack of intercultural communication and students’ interest on the students’ demotivation. The article also examines the mediating role of students’ demotivation amongresistance to innovation, lack of intercultural communication, lack of students’ interest and failure of the English education system in China. This study has gathered the data using survey questionnaires and analyzed the collected data using smart-PLS. The results exposed that the resistance to innovation, lack of intercultural communication and students’ interest have a significant and positive linkage with students’ demotivation. The findings also indicated that students’ demotivation significantly mediates among resistance to innovation, lack of intercultural communication, lack of students’ interest and failure of the English education system in China. This study guides the policymakers to develop the policies related to improving the English education system in China using innovation that enhances student interest and motivation.